Cryptosporidium Infection and Associated Risk Factors among Cattle in the Central Region of Ghana - Kwabena Dankwa; Patrick K. Feglo; Samuel V. Nuvor; Michael Aggrey-Korsah; Mohamed Mutocheluh (Journal of Parasitology Research)
Cryptosporidium species infects a wide number of animals including livestock all over the world. The current study was done to determine the prevalence and risk factors of Cryptosporidium infection among cattle in the Central Region of Ghana. Two hundred and eighty-seven (287) faecal samples were randomly collected from animals on eight cattle farms in four districts across two agroecological zones. A commercial enzyme-linked immunosorbent assay kit (CoproELISA, Savyon® Diagnostics Ltd., Israel) for Cryptosporidium was used in the detection of Cryptosporidium antigens in faecal samples. Characteristics of the animals such as age, sex, and location, as well as consistency of faecal samples, were collected. Pearson’s chi-square or Fisher’s exact test was used to determine the association between explanatory variables and Cryptosporidium infection while a logistic regression model was also used to determine the risk of infection. The overall prevalence of Cryptosporidium infection was 23.7% (95% CI, 18.7-28.6). Prevalence was significantly higher (p=0.049) among cattle aged 12-month old and above compared to those under 12 months of age. Among the four districts in the study area, Cape Coast metropolis recorded a significantly higher prevalence (60.5%; CI, 49.3-71.8), (p<0.001) compared to the other three. Furthermore, a significant association was observed between the consistency of faecal samples and Cryptosporidium infection (p=0.042). The prevalence of Cryptosporidium infection was also significantly higher among cattle from the coastal savanna zone (26.9%; 95% CI, 21.0-32.8) compared to those from the semideciduous forest area (p=0.017). Cattle in the forest zone had a lower risk of being infected with the parasite compared to those from the coastal savanna zone (OR 0.408; 95% CI, 0.182-0.915). In conclusion, Cryptosporidium was prevalent among cattle in the Central Region of Ghana. A higher prevalence of Cryptosporidium infection occurred in older animals and among animals in the coastal agroecological zone. The area of location and age of animals were identified as risk factors for Cryptosporidium infection in the Central Region of Ghana.